2008
DOI: 10.1002/nur.20298
|View full text |Cite
|
Sign up to set email alerts
|

Life course theory as a framework to examine becoming a mother of a medically fragile preterm infant

Abstract: Life course theory, a sociological framework, was used to analyze the phenomenon of becoming a mother, with longitudinal narrative data from 34 women who gave birth prematurely after a highrisk pregnancy, and whose infant became medically fragile. Women faced challenges of mistimed birth and mothering a technologically-dependent infant. Before social ties were established, legal and biological ties required mothers to make critical decisions about their infants. Liminality characterized mothers' early involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 42 publications
5
63
0
4
Order By: Relevance
“…This finding is similar to studies done elsewhere that found that mothers of infants cared for in NICUs perceive technological interventions as ensuring survival. 5,26,27 In addition, the caregivers also thought that the experience of having their infants on bCPAP cleared the misconceptions about bCPAP's lethality. The caregivers in this study described the disruption of parent-infant bonding caused by bCPAP treatment and Chatinkha nursery's visiting policy (every 3 hours) as major sources of stress.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to studies done elsewhere that found that mothers of infants cared for in NICUs perceive technological interventions as ensuring survival. 5,26,27 In addition, the caregivers also thought that the experience of having their infants on bCPAP cleared the misconceptions about bCPAP's lethality. The caregivers in this study described the disruption of parent-infant bonding caused by bCPAP treatment and Chatinkha nursery's visiting policy (every 3 hours) as major sources of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Research employing the life course framework is diverse, from mother-infant health (e.g., Black et al 2009) to child development (Caspi et al 1988, Cooksey et al 1997) and life course trajectories of criminals (e.g., Sampson and Laub 2005). Other research has looked at the impact of the Great Depression on the lives of children who lived through it at different ages (Elder 1974).…”
Section: The Life Course Frameworkmentioning
confidence: 99%
“…In one example, LCT was used to analyze experiences of premature infants’ mothers. The mothers reported experiencing difficulties with making care decisions because they lacked the social and biological ties to their acutely-ill, premature infants (Black, Holditch-Davis, & Miles, 2009). However, no studies have been conducted to represent the LCT of families dealing with their acutely ill child or the healthcare team.…”
Section: Life Course Trajectory (Lct) Theoretical Approachmentioning
confidence: 99%